Understanding Rhetorical Figures Through Multimodal Picture Book Reading (Preučevanje otroške in mladinske književnosti, 2025)
The paper sheds light on the importance of multimodality and considering different codes of communication for constructing meanings with literary and informative reading material. Multimodality is about different codes of communication (linguistic, visual, spatial, gestural, auditory, etc.) and how these are connected in a single medium, e.g. a book. This differs from multimediality, which is an interweaving of different media and their specifics. Codes of communication can be classified according to the senses through which we receive information related to various forms of art. All multimodal analyses of fiction show that illustrations influence the understanding of a story and that it (at least partially) changes or more precisely presents the fundamental morphological characteristics of the texts: the literary time, literary space, literary characters, etc. The theoretical background on multimodality and the understanding of metaphors was empirically tested on students of elementary education with Levi Pinfold's picture book The Black Dog (2011).